Has Economic Policy Uncertainty Slowed Down the World Economy? - Bloom, Nicholas (World Bank, Washington, DC, 2013)
This study details the effects of policy conflicts and fiscal crises in the United States and Europe. The impact of economic policy on the economy is measured to generate a proxy for policy uncertainty using three groups of observable measures and combining them into one index of Economic Policy Uncertainty (EPU). This is achieved by (1) compiling newspaper coverage of policy-related economic uncertainty in ten major US newspapers; (2) depicting accurate reflections of federal tax code provisions which are set to expire in a few years according to the Congressional Budget Office list; and (3) aggregating and exanimating disagreements among economic forecasters in the Philadelphia Federal Reserve’s Survey of Professional Forecasters. Looking ahead, the authors conclude that economic policy uncertainty is the new normal in the United States, Europe and in OECD countries as well.